2017
DOI: 10.1088/1741-4326/aa6d25
|View full text |Cite
|
Sign up to set email alerts
|

Edge and divertor plasma: detachment, stability, and plasma-wall interactions

Abstract: The processes involving edge plasma and plasma-material interactions in magnetic fusion devices are very multifaceted and include a wide spectrum of phenomena ranging from plasma turbulence and meso-scale stability, recycling and transport processes of hydrogen species in the wall material, to the modification of wall material properties. In many cases these processes are strongly coupled and exhibit synergistic effects. Here we present the results of our studies of a wide range of edge plasma related issues: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 51 publications
4
20
0
Order By: Relevance
“…In most of the 2-D numerical simulations performed so far (in particular, in support of ITER), the cross-field plasma transport coefficients are assumed to be constant in time. A bifurcation-like transition to detachment may also be related to a breakdown of the quasi-equilibrium between the absorption and desorption processes on the plasma-facing components (Krasheninnikov et al 2017b). A large amount of hydrogen, at least in carbon wall tokamaks, is usually stored in the first wall material.…”
Section: Transition To the Detached Divertor Regimementioning
confidence: 99%
“…In most of the 2-D numerical simulations performed so far (in particular, in support of ITER), the cross-field plasma transport coefficients are assumed to be constant in time. A bifurcation-like transition to detachment may also be related to a breakdown of the quasi-equilibrium between the absorption and desorption processes on the plasma-facing components (Krasheninnikov et al 2017b). A large amount of hydrogen, at least in carbon wall tokamaks, is usually stored in the first wall material.…”
Section: Transition To the Detached Divertor Regimementioning
confidence: 99%
“…However, in order to bring the simulations closer to experimental situations in divertor operation, it is necessary to include recycling physics in the models. This is mandatory to address regimes relevant for next‐step machines, high recycling regimes, and even detached regimes, all the more because experimental evidence points towards changes of transport with the density regimes . Several groups have implemented neutral models in their code, either in 2D or 3D codes: a simplified kinetic model in GBS and a fluid model in BOUT++ .…”
Section: Introductionmentioning
confidence: 99%
“…As a first step, we focus on the plasma blob formation caused by edge turbulence by applying a two‐dimensional (2D) interchange turbulence model to the edge and the SOL regions. The 2D model consists of the density and vorticity equations with E × B drift and diamagnetic drift, which are considered to have a direct relation to the plasma blob formation and transport . The computational domain is set as a simple 2D slab geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that non-diffusive radial transport is also important. [7][8][9][10][11][12] The plasma blob has been observed in the various fusion devices. [7,13,14] However, the formation mechanism of the plasma blob itself and also the effect of the plasma blob on the impurity transport have not yet been understood well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation